Compatibility Test of Thermophilic Microbes Isolated from Mudiak Sapan Hot Springs - putri auliya (Jurnal Serambi Biologi, 2023)
Thermophilic bacteria are bacteria that can grow at high temperatures (45-70°C) and have the potential to produce heat-stable enzymes and are capable of producing bioethanol. Thermophilic microbes can be isolated from geothermal environments such as the Mudiak Sapan hot springs. In order to maximize its potential, a compatible test between isolates that have been isolated, namely MS isolate (Mudiak Sapan) is required. This study aims to test the compatibility of thermophilic microbes isolated from Mudiak Sapan hot springs. This research is a descriptive study using the pour plate method. Compatibility test of MS isolates isolated from Mudiak Sapan hot springs, Jorong Balun, Nagari Pakan Rabaa, Koto Parik Gadang District in Ateh. The results of this study obtained 6 combinations of bicultural isolates, namely: (MS 9 & MS 4), (MS 12 & MS 4), (MS 18 & MS 4), (MS 17 & MS 4), (MS 9 & MSS 8) , (MS 12 & MSS 8) are indicated to be compatible in the absence of a clear zone and synergize with one another.